Genome Mining of Oxidation Modules in trans‐Acyltransferase Polyketide Synthases Reveals a Culturable Source for Lobatamides. Issue 20 (19th March 2020) - Ueoka, Reiko; Meoded, Roy A.; Gran‐Scheuch, Alejandro; Bhushan, Agneya; Fraaije, Marco W.; Piel, Jörn
Abstract: Bacterial trans ‐acyltransferase polyketide synthases ( trans ‐AT PKSs) are multimodular megaenzymes that biosynthesize many bioactive natural products. They contain a remarkable range of domains and module types that introduce different substituents into growing polyketide chains. As one such modification, we recently reported Baeyer–Villiger‐type oxygen insertion into nascent polyketide backbones, thereby generating malonyl thioester intermediates. In this work, genome mining focusing on architecturally diverse oxidation modules in trans ‐AT PKSs led us to the culturable plant symbiont Gynuella sunshinyii, which harbors two distinct modules in one orphan PKS. The PKS product was revealed to be lobatamide A, a potent cytotoxin previously only known from a marine tunicate. Biochemical studies show that one module generates glycolyl thioester intermediates, while the other is proposed to be involved in oxime formation. The data suggest varied roles of oxygenation modules in the biosynthesis of polyketide scaffolds and support the importance of trans ‐AT PKSs in the specialized metabolism of symbiotic bacteria. Abstract : O where art thou : In the classic model for modular polyketide synthases (PKSs), a small set of reactions generate combinatorially substituted carbon chains. Architecturally diverse PKS modules were identified that diversify polyketides by oxygenation. An orphan PKS with two oxygenase modules from a plant symbiont was found to produce lobatamides, which are in‐chain‐oxygenated oxime‐bearing cytotoxins that were previously only known from a tunicate.